2022
DOI: 10.1038/s41598-022-17037-x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into sperm rheotaxis, agglutination and bundle formation in Sharkasi chickens based on an in vitro study

Abstract: Fertility in birds is dependent on their ability to store adequate populations of viable sperm for extended durations in sperm storage tubules (SSTs). The exact mechanisms by which sperm enter, reside, and egress from the SSTs are still controversial. Sharkasi chicken sperm showed a high tendency to agglutinate, forming motile thread-like bundles comprising many cells. Since it is difficult to observe sperm motility and behavior inside the opaque oviduct, we employed a microfluidic device with a microchannel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…The gradual egress of spermatozoa into the oviduct lumen is thought to be caused by random detachment of agglutinated sperm 4 . Therefore, we suggest that the agglutination behavior of Sharkasi sperm gives them superiority over Dandarawi sperm when present in a competitive situation to fertilize the ova because sperm are lost from the SSTs when the agglutination state is not sustained.. El-sherry et al 26 reported that sperm agglutination in motile bundles increases the number of sperm showing positive rheotaxis which is suggested to benefit sperm during the vaginal selection process (passage of sperm through the vagina) and the SSts uptake (sperm penetration into SSTs). According to this assumption, more sperm from Sharkasi will occupy vacant areas of the SSTs compared to Dandarawi sperm.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The gradual egress of spermatozoa into the oviduct lumen is thought to be caused by random detachment of agglutinated sperm 4 . Therefore, we suggest that the agglutination behavior of Sharkasi sperm gives them superiority over Dandarawi sperm when present in a competitive situation to fertilize the ova because sperm are lost from the SSTs when the agglutination state is not sustained.. El-sherry et al 26 reported that sperm agglutination in motile bundles increases the number of sperm showing positive rheotaxis which is suggested to benefit sperm during the vaginal selection process (passage of sperm through the vagina) and the SSts uptake (sperm penetration into SSTs). According to this assumption, more sperm from Sharkasi will occupy vacant areas of the SSTs compared to Dandarawi sperm.…”
Section: Discussionmentioning
confidence: 85%
“…1 and 2 ). A detailed description of the sperm bundles is reported by El-sherry et al 26 . With time, the bundles grow and increase in diameter and length (Supplementary Video 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations